CFD modelling of a mixing chamber for the realisation of functionally graded scaffolds - G. Mattei; G. Vozzi (Computers and Chemical Engineering, 2015)
Biological tissues are characterised by spatially distributed gradients, intricately linked with functions. It widely accepted that ideal tissue engineered scaffolds should exhibit similar functional gradients to promote successful tissue regeneration. Focusing on bone, in previous work we proposed simple methods to obtain osteochondral functionally graded scaffolds (FGSs), starting from homogeneous suspensions of hydroxyapatite (HA) particles in gelatin solutions. With the main aim of developing an automated device to fabricate FGSs, this work is focused on designing a stirred tank to obtain homogeneous HA-gelatin suspensions. The HA particles transport within the gelatin solution was investigated through computational fluid dynamics (CFD) modelling. First, the steady-state flow field was solved for the continuous phase only. Then, it was used as a starting point for solving the multi-phase transient simulation. CFD results showed that the proposed tank geometry and setup allow for obtaining a homogeneous suspension of HA micro-particles within the gelatin solution.
Keywords: Bioengineering

Combining Inkjet Printing and Sol-Gel chemistry for Making pH-Sensitive surfaces - G. Orsi; C. De Maria; F. Montemurro; Chauhan, V.; Aylott, J.; G. Vozzi (Current topics in medicinal chemistry, 2015)
Keywords: Bioengineering

Characterization of 3-Iodothyronamine In Vitro Dynamics by Mathematical Modeling - G. Orsi; Ghelardoni, S.; Saba, A.; R. Zucca; G. Vozzi (Cell biochemistry and biophysics, 2014)

Collagen-gelatin-genipin-hydroxyapatite composite scaffolds colonized by human primary osteoblasts are suitable for bone tissue engineering applications: In vitro evidences - G. Vozzi; Corallo, C.; Carta, S.; Fortina, M.; Gattazzo, F.; Galletti, M.; N. Giordano (Journal of Biomedical Materials Research Part A, 2014)

CREPE: mathematical model for CRosstalking of Endothelial cells and hePatocytE metabolism - Valvano, G; G. Orsi; M. A. Guzzardi; Vozzi, F.; G. Vozzi (IEEE Transactions of Biomedical Engineeirng, 2014)
Keywords: Bioengineering

Characterization of 3-Iodothyronamine In Vitro Dynamics by Mathematical Modeling - G. Orsi; S. Ghelardoni; A. Saba; R. Zucca; G. Vozzi (Cell Biochem Biophys, 2013)
Keywords: Bioengineering

Collagen VI regulates satellite cell self-renewal and muscle regeneration - Urciuolo, A; M. Quarta; V. Morbidoni; Gattazzo, F; S. Molon; P. Grumati; F. Montemurro; F. S. Tedesco; B. Blaauw; G. Cossu; G. Vozzi; T. A. Rando; et al. (Nat Commun, 2013)
Keywords: Bioengineering

Collagen-gelatin-genipin-hydroxyapatite composite scaffolds colonized by human primary osteoblasts are suitable for bone tissue engineering applications: In vitro evidences - G. Vozzi; C. Corallo; S. Carta; M. Fortina; Gattazzo, F; M. Galletti; N. Giordano (J Biomed Mater Res A, 2013)
Keywords: Bioengineering

Collagen‐gelatin‐genipin‐hydroxyapatite composite scaffolds colonized by human primary osteoblasts are suitable for bone tissue engineering applications: In vitro evidences - G. Vozzi; C. Corallo; S. Carta; M. Fortina; Gattazzo, F; M. Galletti; N. Giordano (Journal of Biomedical Materials Research Part A, 2013)
Keywords: Bioengineering

Characterization and modeling of mechanical behavior a discrete gradient structure - Caputo, M; G. Vozzi; G. Mattei (Congresso Nazionale di Bioingegneria 2012 Atti, 2012)
Keywords: Bioengineering

Cooperation of Biological and Mechanical Signals in Cardiac Progenitor Cell Differentiation - S. Pagliari; A.C. Vilela-Silva; G. Forte; F. Pagliari; C. Mandoli; G. Vozzi; S. Pietronave; M. Prat; S. Licoccia; A. Ahluwalia; E. Traversa; M. Minieri; et al. (ADVANCED MATERIALS, 2011)
Keywords: Bioengineering

Chitosan/gelatin blends for biomedical applications - PULIERI, E; V. Chiono; G. Ciardelli; G. Vozzi; A. Ahluwalia; C. Domenici; Vozzi, F.; P. Giusti (JOURNAL OF BIOMEDICAL MATERIALS RESEARCH. PART A, 2008)
Keywords: Bioengineering

Comparative study of porous and engineered biomaterials - Mattioli-Belmonte, M.; K KYRIAKIDOU; LUCARINI, G; ZIZZI, A; A. Ahluwalia; G. Vozzi (INTERNAL MEDICINE, 2008)
Keywords: Bioengineering

Composite polyurethane and carbon black bimorph bender microfabricated with pressure assisted microsyringe (PAM) for biomedical applications - Tartarisco, G.; G. GALLONE; F. Carpi; G. Vozzi (2008)
Keywords: Bioengineering

Controlled in vitro growth of cell microtubes: towards the realisation of artificial microvessels - Migliore, A.; Vozzi, F.; G. Vozzi; A. Ahluwalia (BIOMEDICAL MICRODEVICES, 2008)
Keywords: Bioengineering

Criticality of the Biological and Physical Stimuli Array Inducing Resident Cardiac Stem Cell Determination - G. Forte; CAROTENUTO, F; F. Pagliari; S. Pagliari; COSSA, P; FIACCAVENTO, R; A. Ahluwalia; G. Vozzi; Vinci, B.; SERAFINO, A; RINALDI, A; E. Traversa; et al. (STEM CELLS, 2008)
Keywords: Bioengineering

Cardiac and Mesenchymal Stem Cell Growth and Selective Differentiation on Three Dimensional Bioerodable Scaffolds - G. Forte; CAROTENUTO, F; G. Vozzi; COSSA, P; FIACCAVENTO, R; M. Minieri; F. Pagliari; S. Pagliari; Romano, R.; A. Ahluwalia; E. Traversa; P. Di Nardo (Termis Eu-Meeting London (UK) 4-7 September 2007 Tissue Engineering 2007, 13 (7): 1647, 2007)
Keywords: Bioengineering